Heat Accumulation Mechanism of the Gaoyang Carbonatite Geothermal Field, Hebei Province, North China - Zhang, Baojian; Wang, Siqi; Kang, Fengxin; Wu, Yanqiu; Li, Yanyan; Gao, Jun; Yuan, Wenzhen; Xing, Yifei (Frontiers in Earth Science, 2022)
From 2019 to 2021, we constructed two high-productivity geothermal wells with wellhead temperatures of 109.2 and 123.4°C in the Gaoyang geothermal field. Based on the two wells, it was proved that Gaoyang is a medium-temperature carbonate geothermal field with great development potential. The article reported the latest exploration achievements of deep buried hill geothermal resources in the geothermal field. The productivity of D34 and D35 geothermal wells were evaluated by James end-pressure method: the total flow of steam–water mixture was 234.59–331.92 (t/h), the dryness was 1.36–2.03%, and the single-well power generation potential was 2.10–2.55 MW. Combined with those results, the heat control factors and heat accumulation mechanism of the deep carbonatite geothermal field were confirmed. The westward subduction of the Pacific plate caused obvious damage to the eastern North China Craton and greatly reduced the thickness of the lithosphere and crust. This process facilitated the conduction of mantle-derived heat to shallow crust. Deep strike-slip faults (e.g., Maxi fault) cut through the lithosphere, leading the deep mantle-derived heat and magma to migrate into the crust. The heat accumulated from the depression with low thermal conductivity to the uplift with high thermal conductivity. Groundwater was heated up by deep cycle and convection along faults. The catchment of regional karst groundwater also had a certain effect on the heat accumulation. The Gaoyang geothermal field was formed by these factors.